Propagating arid fruits commercially - Singh, A K (Indian Horticulture, 2019)
The importance of arid fruits is increasing because people are realizing the importance of new useful bioactive compounds, low calories, sweetness, insecticidal compounds and gamma linolenic acid. Planting of these hardy species can stabilize productivity on marginal lands. Looking into the importance of these underutilized fruits, the demand for its planting material is increasing day-by-day. To meet the demand of genuine planting material, procedure of vegetative propagation of underutilized fruits has been standardized for generating quality planting materials. From various studies for optimization of period of vegetative propagation and quality of scion, shoots and rootstocks of these fruit crops have been summarized, particularly the methods which can be used for commercial multiplication of arid and semi-arid underutilized fruits (jamun, bael, tamarind, khirni, chironji, custard apple, wood apple, karonda, gonda, mahua, pilu, ker etc.).